Atherogenic dyslipidemia and insulin resistance associated with nonalcohol hepatic steatosis: comparison, contrast, and differentiated therapy - L. B. Lazebnik; L. A. Zvenigorodskaya; N. V. Melnikova; E. G. Egorova; S. G. Khomeriki (Кардиоваскулярная терапия и профилактика, 2009)
Aim. To study clinical, functional, morphological and pharmacological features of hepatic pathology in patients with non-alcohol hepatic steatosis (NAHS), combined with atherogenic dyslipidemia (ADL) and/or insulin resistance (IR).Material and methods. The study included 240 patients with NAHS: 100 with DL but no IR; 78 — with IR but no DL; 14 — with Type 2 diabetes mellitus (DM-2), IR and DL; 48 — without DL or IR (controls). All participants underwent standard clinical examination, blood biochemistry and hepatitis virus marker assessment, oral glucose tolerance and HOMA test, abdominal ultrasound and hepatic puncture biopsy.Results. NAHS clinical course was non-specific. Cytolysis syndrome activity was maximal in DM-2 patients. All patients had cholestasis syndrome manifestations, maximal in IR individuals. Hepatic morphology was characterized by large-drop fat dystrophy, inflammation and fibrosis. In patients with disturbed carbohydrate and lipid metabolism, hepatocyte nuclear changes and nuclear polymorphism were observed, respectively. In participants receiving a combination of statins and ezetimibe, blood lipid profile improved at the second week of the treatment. IR patients received metformin, with positive dynamics of hepatic morphology and function.Conclusion. Despite no clinical differences between NAHS patients with ADL and IR, the latter are characterized by more aggressive morphological changes. Differentiated ethiotropic therapy of NAHS should take ADL and IR presence into account.